PENGEMBANGAN SET PRAKTIKUM BERBASIS DATA LOGGER PADA PEMBELAJARAN FISIKA SMA KELAS XII MATERI RANGKAIAN ARUS LISTRIK SEARAH - Dwiokta Muthia Putri Karlina; Desnita Desnita; Hadi Nasbey (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The aim of this research was to developed direct current circuits practical set based on data logger on physics learning for 12st grade. The method used in this research was research and development, that is: (1) research and information gathering; (2) planning; (3) develop of the initial product; (4) field testing and product revision; (5) final product revision; and (6) dissemination and implementation. Data collection techniques used in this research was: questionnaires and observation. The respondents of this research were the respondents experts consist of physics experts, media experts, a high school physics teacher respondents and also field test was done by the students of SMA Negeri 2 Bekasi and SMA Kartini 1 Jakarta. Based on the results of data analysis and discussion concluded that development of practical set in general has been very good with the suitability of the results of expert judgment and field test. The result of practical set validation by media expert was 86,12%, physics expert was 88,75%, physics teacher was 92,37% which means the set was very great. The result of preliminary field testing to studensts of SMA Negeri 2 Bekasi was 82.80%, while the result of operasional field testing to students of SMA Kartini 1 Jakarta was 84.05% which means the set was very great. Both of field test showed that the product received a positive response from the students. Keywords: research and development, practical set, data logger, direct current circuits.